Duloxetine and escitalopram for hot flushes: efficacy and compliance in breast cancer survivors. (3rd March 2016) - Biglia, N.; Bounous, V.E.; Susini, T.; Pecchio, S.; Sgro, L.G.; Tuninetti, V.; Torta, R.
Abstract : Selective serotonin reuptake inhibitors (SSRI) and serotonin–norepinephrine reuptake inhibitors (SNRI) might be an effective treatment for hot flushes (HFs) in breast cancer survivors (BCSs). This study aims to compare the efficacy and tolerability of duloxetine (SNRI) versus escitalopram (SSRI) in reducing frequency and severity of HFs in BCSs and to assess the effect on depression. Thirty‐four symptomatic BCSs with emotional impairment received randomly duloxetine 60 mg daily or escitalopram 20 mg daily for 12 weeks. Patients were asked to record in a diary HF frequency and severity at baseline and after 4 and 12 weeks of treatment. Depression was evaluated through validated questionnaires (Beck Depression Inventory and Montgomery Asberg Depression Rating Scale) at baseline and after 4 and 12 weeks of treatment. Both drugs showed a significant reduction of HF frequency and severity after 12 weeks of treatment with no significant difference between the two groups. A significant improvement in depression symptoms was observed at the end of the study period within both the groups, without difference between the two drugs. In conclusion, escitalopram and duloxetine are both effective treatment for the relief of HFs in BCSs, with similar beneficial effect. A significant improvement of depression was obtained with no major side effects.